Original-translation Linguistic Contrastive Analysis according to the American story ‘ The Adventures of Tom Sawyer’ by Mark Twain - Charkviani, Nunu; Rusadze, Irma; Kipiani, Sopio (Bulletin of Akaki Tsereteli State University, 2026)
The article deals with the significance of translation in the point of communication and social-cultural functions. Translation methods create essential conditions to make student’s oral and written speech more authentic. Theoretical and practical materials enable English learners to be creatively free and overcome language barriers-so called interference. The aim of the article is to make a linguistic contrastive analysis of the work ‘The Adventure of Tom Sawyer’ by Mark Twain and its translation. Conducting a linguistic research is one of the methods of teaching literature; It is considered to be a synthesis of transnational and cross-cultural diapasons (ranges). Comparing the examples from the source languages (English and Georgian ) encouraged us to establish those similarities and differences that are characteristic to both languages. So this one represents the second directive of translation of a literary work that is known as a linguistic method.